Composition of Ballast Water from Ships Arriving at Kertih Port, Malaysia with Observations on Port and Offshore Waters, and Notes on Settlement Patterns of Fouling Organisms - Lee Siang Hing; Kesaven Bhubalan; Peck Ying Tan; Rohaida Mat Husain (Universitas Gadjah Mada, 2018)
We investigated plankton composition and water quality of ballast water from seven international ships docked at Kertih Port, Malaysia. Coscinodiscophyceae and cyanobacteria were the dominant phytoplankton found in ballast water samples, whereas copepod nauplii, Oithona sp., Microstella sp. and Paracalanus sp. were the dominant zooplankton. The densities for both phytoplankton and zooplankton in ships’ ballast and port waters were higher than those of offshore samples. All water quality parameters (except Cr) of port samples were within the safety levels prescribed for ports, oil and gas fields (Class 3) by the Malaysia Marine Water Quality Criteria Standard. The study of fouling organisms using PVC panels revealed that brown algae covered 87–95% of the panels’ surface area but they were subsequently succeeded by barnacles, bivalves and red encrusting algae. Barnacle recruitment, however, was greatly influenced by crab predation which left behind a high percentage cover of barnacle bases as calcareous deposits on panels.